Redispersible nanosuspensions as a plausible oral delivery system for curcumin. (December 2021) - Elbaz, Nancy M.; Tatham, Lee M.; Owen, Andrew; Rannard, Steve; McDonald, Tom O.
Abstract: Curcumin is widely used as a nutraceutical ingredient in food and beverage products. It has been reported that curcumin has a broad spectrum of biological activities such as anticancer, anti-inflammatory, antioxidant, and antibacterial effects. Despite the potent therapeutic effect of curcumin, its low aqueous solubility, stability, and oral bioavailability limits its effectiveness. In order to improve the physical and chemical properties of curcumin, we have formulated curcumin as a nanosuspension by using the emulsion templated freeze-drying technique. This approach produces a solid that can be dispersed as required to form a nanosuspension. The formulations were investigated in a screening process using various excipients, resulting in the identification of one curcumin nanosuspension sample which contained only polyethylene glycol (PEG) as the excipient. This formulation exhibited a small diameter (211 nm), low polydispersity (0.06) and zeta potential of −25 mV and was therefore chosen for further in vitro investigations. Various experimental parameters such as active agent and excipient concentrations, and sonication time were varied to tune the size and polydispersity of the chosen formulation. The resulting nanosuspension showed an improved chemical stability at pH values that mimic the gastrointestinal tract. An in vitro bioaccessibility experiment showed that the nanosuspension formulation resulted in more dissolution of the curcumin but this was also coupled with reduced stability. Cytotoxicity studies showed that the nanosuspension offered a reduced cytotoxicity profile compared to the solubilised curcumin on both cell lines investigated. This redispersible curcumin nanosuspension formulation may provide new opportunities for the oral dosing of curcumin. Graphical abstract: Curcumin was formulated as a nanosuspension by an emulsion-templated freeze-drying technique. The curcumin formulation could be redispersed to form a nanosuspension and demonstrated favourable colloidal and chemical stability. Image 1 Highlights: A simple formulation of curcumin that uses a single excipient and forms nanosuspension with an average diameter of 200 nm. The formulation is produced as a dry solid that can be dispersed on-demand to form the nanoparticles. The nanosuspension show improved chemical stability compared to solubilised curcumin. The cytotoxicity of the curcumin nanosuspension is similar to the solubilised curcumin but does not require solvent.